Formação de grêmios estudantis em escolas públicas municipais de Bauru - Valente Neto, Alberto Borges [UNESP]; Martinez, Carolina Terruggi [UNESP]; Harms, Camila [UNESP]; Asbahr, Flávia da Silva Ferreira [UNESP]; Bulhões, Larissa Figueiredo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work is an exposure about the students union project carried out by students of Psychology of Unesp- campus Bauru, along with officials from elementary municipal schools in the same city. The project is a result of a partnership between the City Department of Education with the Department of Psychology of the Unesp promote advances in democratic management of the school system as well as providing a theoretical and practical training opportunities for graduate students. The project has made the implementation of students associations in all network schools and has sought to advance the student participation through these spaces. Aiming to contribute to the democratic management of schools, the project has carried out actions with the stud participating in the union discussions, survey of school needs, dialogue with other students about what is needed to improve the school, claims to school managers and others, always seeking to increase student participation in school decisions. For this, the project has meeting with students association in schools, planning meetings of the actions, supervision groups working in schools, theoretical training spaces and events like the visit of students to Unesp and the Youth Forum of Education Week in Bauru. The work has been challenging, given the large extent to which it operates, but could significantly advance each year of operation.

O presente trabalho faz uma exposição acerca do projeto de extensão Grêmios Estudantis realizado por alunos do curso de Psicologia da Unesp- campus Bauru, juntamente com funcionários das escolas municipais de ensino fundamental da mesma cidade. O projeto é fruto de uma parceria da Secretaria Municipal de Educação com o Departamento de Psicologia da Unesp - campus Bauru, visando promover avanços na gestão democrática das escolas da rede, bem como proporcionar um espaço de formação teórico-prático para os estudantes da graduação. O projeto realizou a implementação de grêmios estudantis em todas as escolas da rede e tem buscado avançar na participação estudantil por meio destes espaços. Tendo como objetivo contribuir para a gestão democrática das escolas, o projeto tem realizado ações com os estudantes que participam do grêmio como discussões sobre representatividade, levantamento de necessidades da escola, diálogo com os demais estudantes sobre o que é necessário para melhorar a escola, reivindicações aos gestores da escola e outras, sempre buscando ampliar a participação dos estudantes nas decisões da escola. Para tanto, o projeto conta com encontros com os alunos do grêmio nas escolas, reuniões de planejamento das ações, supervisões aos grupos que atuam nas escolas, espaços de formação teórica e eventos como a visita das crianças à Unesp e o Fórum Infanto Juvenil na Semana da Educação de Bauru. O trabalho tem sido desafiador, dada a grande extensão em que atua, mas pôde avançar significativamente a cada ano de atuação.
Keywords: School psychology; Management; Students union; Psicologia escolar; Gestão democrática; Grêmio estudantil